The core 4 : embrace your body, own your power - Gaudreau, Steph (Harper One, 2019)
"In THE CORE 4 Steph finally offers women a strong body and mind achieved through minimal time on the treadmill, simple workouts, targeted nutrition (that is also delicious!), and mindset practices with clear results. When you focus on The Core 4--Eat Nourishing Foods, Move with Intention, Recharge Your Energy, and Empower Your Mind--you give yourself the gifts of care, strength, and resiliency, and take a powerful step toward the life you want."--Amazon.